Utilization of Geographic Information System (GIS) for Determining the Accordance of the Marine Tourism Pinangsori Sub-district, Tapanuli Tengah District - Tiara Dewi Bugis; Insaniah Rahimah; Fitri Ariani; Emma Suri Yanti Siregar (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Geographical Information System (GIS) is a computer system used to collect, examine, integrate, and analyze information related to surface of the earth. One of the benefits of using GIS is to determine the suitability of a marine tourism area, which is the purpose of this study, the results showed that the Pinangsori sub-districts